Optimized Nanolubricant for Friction Reduction - Abdullah, Muhammad Ilman Hakimi Chua; Abdollah, Mohd Fadzli bin; Amiruddin, Hilmi; Mat Nuri, Nur Rashid (2013)
In Malaysia, capability of nanoparticles as lubricating oil additive to improve the performance of diesel engine oil has not yet been studied extensively. Therefore, this paper presents the experimental results for conventional diesel engine oil enriched with optimized nanoparticles